Interleukin-15 Affects Patient Survival through Natural Killer Cell Recovery after Autologous Hematopoietic Stem Cell Transplantation for Non-Hodgkin Lymphomas. (18th April 2010) - Porrata, Luis F.; Inwards, David J.; Micallef, Ivana N.; Johnston, Patrick B.; Ansell, Stephen M.; Hogan, William J.; Markovic, Svetomir N.
Abstract : Natural killer cells at day 15 (NK-15), after autologous peripheral blood hematopoietic stem cell transplantation (APHSCT), is a prognostic factor for overall survival (OS) and progression-free survival (PFS) in non-Hodgkin lymphoma (NHL). The potential role of the immunologic (homeostatic) environment affecting NK-15 recovery and survival post-APHSCT has not been fully studied. Therefore, we evaluate prospectively the cytokine profile in 50 NHL patients treated with APHSCT. Patients with an interleukin-15 (IL- 15 ) ≥ 76.5  pg/mL at day 15 post-APHSCT experienced superior OS and PFS compared with those who did not; median OS; not reached versus 19.2 months, P < .002 ; and median PFS; not reached versus 6.8 months, P < .002, respectively. IL-15 was found to correlate with (r s = 0.7, P < .0001 ) NK-15. Multivariate analysis showed only NK-15 as a prognostic factor for survival, suggesting that the survival benefit observed by IL-15 is most likely mediated by enhanced NK cell recovery post-APHSCT.